Metallographic and Magentic Properties of a Yamato Iron Meteorite─Yamato-75-105 - Nagata, Takesi; Fisher, Robert M.; Sugiura, Naoji (1976)
P(論文) A Yamato iron meteroite, Yamato-75-105, examined chemically, metallographically and magnetically, has revealed that the major elements of the metal base of this iron meteorite are 5.65% Ni, 1.0% P, and 0.52% Co, in addition to Fe occupying the most parts. From the chemical composition and the microstructure, this iron meteorite can be classified as a reheated hexahedrite, i. e. a Ni-poor ataxite. An "ablation zone" about 2mm in thickness on the flat surface indicates an extensive reheating on entry into the earth's atmosphere although traces of the original single-crystal features remain. Within the matrix of kamacite (95% Fe and 5% Ni) composition, Fe-Ni phosphide (schribersite 75% Fe, 10% Ni and 15% P) grains are enveloped by high-P kamacite of α-phase (91% Fe, 7% Ni and 2% P). These structures suggest that this meteorite specimen was reheated to above 1000℃. The acicular grain structure of the kamacite matrix indicates a rapid cooling rate after the reheating. Both metallographic and magnetic analyses have consistently revealed the above-mentioned conclusion. departmental bulletin paper